WNK3 kinase maintains neuronal excitability by reducing inwardly rectifying K+ conductance in layer V pyramidal neurons of mouse medial prefrontal cortex - Sinha, Adya Saran; Wang, Tianying; Watanabe, Miho; Hosoi, Yasushi; Sohara, Eisei; Akita, Tenpei; Uchida, Shinichi; Fukuda, Atsuo (Frontiers in Molecular Neuroscience, 2022)
The with-no-lysine (WNK) family of serine-threonine kinases and its downstream kinases of STE20/SPS1-related proline/alanine-rich kinase (SPAK) and oxidative stress responsive kinase-1 (OSR1) may regulate intracellular Cl homeostasis through phosphorylation of cation-Cl− co-transporters. WNK3 is expressed in fetal and postnatal brains and its expression level increases during development. Its roles in neurons, however, remain uncertain. Using WNK3 knockout (KO) mice, we investigated the role of WNK3 in regulation of the intracellular Cl− concentration ([Cl-]i) and the excitability of layer V pyramidal neurons in the medial prefrontal cortex (mPFC). Gramicidin-perforated patch-clamp recordings in neurons from acute slice preparation at the postnatal day 21 indicated a significantly depolarized reversal potential for GABAA receptor-mediated currents by 6 mV, corresponding to the higher [Cl]i level by 4 mM, in KO mice than wildtype littermates. However, phosphorylation levels of SPAK and OSR1 and those of neuronal Na+-K+-2Cl− cotransporter NKCC1 and K+-Cl− cotransporter KCC2 did not significantly differ between KO and wildtype mice. Meanwhile, the resting membrane potential of neurons was more hyperpolarized by 7 mV, and the minimum stimulus current necessary for firing induction was increased in KO mice. These were due to an increased inwardly rectifying K+ conductance, mediated by classical inwardly rectifying (Kir) channels, in KO neurons. Introduction of an active form of WNK3 into the recording neurons reversed these changes. The duration of individual action potential spikes was also prolonged in KO neurons. Moreover, the frequency of miniature excitatory postsynaptic currents (mEPSCs) was reduced, whereas that of inhibitory currents (mIPSCs) was slightly increased in KO neurons. These results suggest that WNK3 in pyramidal neurons plays a critical role in maintenance of neuronal excitability by reducing resting membrane K+ conductance and increasing the number of excitatory synaptic inputs, with a weak effect on intracellular Cl− homeostasis. The impact of these developmental changes in membrane and synaptic properties was manifested as behavioral deficits in prepulse inhibition, a measure of sensorimotor gating involving multiple brain regions including the mPFC, in KO. Thus, the basal function of WNK3 would be maintenance and/or development of both intrinsic and synaptic excitabilities.